INTEGRATED BUDDHISM TO PROMOTE PEACEFUL POLITICAL CULTURE AMONG THE PEOPLE OF BANG KRANG MUNICIPALITY, MUEANG NONTHABURI DISTRICT, NONTHABURI PROVINCE - Meesaku, Vanida; Bhalakula, Ancucha; Akhomtiro, Phra SamuAkhom (Journal of MCU Phetchaburi Review, 2025)
This mixed-method research aimed to 1) study the level of peaceful political culture; 2) study the relationship between Saraniyadhamma and peaceful political culture; 3) study the relationship between Saraniyadhamma and peaceful political culture; and 3) propose Buddhist integration to promote peaceful political culture. The sample consisted of 393 eligible voters aged 18 years and over in Bang Krang Municipality and 9 key informants. Data were analyzed using percentages, means, standard deviations, Pearson's product moment correlation coefficients, and descriptive content analysis. The results revealed that 1) the overall level of peaceful political culture was high; 2) the relationship between Saraniyadhamma and peaceful political culture was positive and highly positive; and 3) Buddhist integration to promote peaceful political culture emphasizes developing people's behavior, speech, and thoughts to be kind and respectful of one another. Metta kaya-karma promotes helpful actions; Metta vacikarma emphasizes polite speech to foster understanding; and Metta manokarma is respect for others' opinions and collaborative development. Public welfare instills a sense of public concern. Morality creates discipline and public spirit. Common view creates unity and consensus in joint local development, resulting in peace and sustainability and creating a political culture based on moral principles.